Macro and microanatomy of some organs of a juvenile male Ganges River dolphin (Platanista gangetica spp. gangetica). (5th October 2022) - Shil, Subrata Kumar; Zahangir, Md. Mahiuddin; Das, Bhajan Chandra; Rahman, Mohammad Mahbubur; Yadav, Saroj Kumar; Kibria, Md. Manzoorul; Zonaed Siddiki, AMAM
Abstract: Ganges River dolphins ( Platanista gangetica spp. gangetica ) are air‐breathing, warm‐blooded mammals endemic to the Ganges and Karnaphuli rivers of the Indian subcontinent. Nevertheless, very little basic histomorphological research has been conducted on this endangered species. Therefore, this study aimed to describe the morphological features of different organs of P. gangetica . Despite becoming aquatic animals, they showed similarities with terrestrial mammals, such as the pair of lungs and an apical bronchus in the respiratory system, which are pretty standard in ruminants and pigs. However, unlike the terrestrial animal, the tracheobronchial tree was stiffer due to circularly arranged anastomosing plates of the hyaline cartilaginous ring in the trachea, cartilaginous plates in the bronchiole, and thick alveolar septa. The digestive system showed a three‐chambered mechanical and glandular stomach similar to the artiodactyles. However, the intestine showed smaller caecum like the monogastric mammal. The urogenital system showed lobulated kidneys, a urinary bladder, a fibroelastic penis with sigmoid flexure, and a long urethral process similar to some terrestrial ruminants. Considering the aquatic environment, all those modifications, unlike terrestrial mammals, are necessary for their adaptation. Thus, this research will broadly help our clinicians and conservationist to take further steps toward disease diagnosis and monitoring of marine health of this endangered species.